Yttrium-90 production via neutron irradiation at TRIGA Puspati research reactor - Hafiz, Shazmin Hamimi; Mohamed, Faizal; Mohd Fadzil, Syazwani; Itam Sulaiman, Nurul Nafiqah; Yahya, Mohd Syukri; Abdul Khalil, Muhammad Husamuddin; Hamzah, Na’im Syauqi; Mohd Noor, Noramaliza; Idris, Mohd Idzat (Springer Nature, 2026)
This study presents the optimized production of Yttrium-90 via neutron irradiation of Yttrium-89 using the PUSPATI TRIGA reactor however not for medical embolization. By varying irradiation time, high-activity Y-90 with a beta activity of 3.56 ± 0.02 × 103 Bq/g was achieved. Multiple analytical techniques confirmed the production of Y-90 and were used to evaluate its activity and composition. The findings support the feasibility of Y-90 production using a research reactor, with potential for further optimization under local operating conditions.